Auditoría financiera a los rubros que conforman el pasivo de una unidad educativa experimental privada en la ciudad de Guayaquil al 31 de diciembre de 2008 - María, Carranza J. (2010)
This work was developed through audit procedures and tests and statistics that allowed us to give an opinion on the preparation and fair presentation of the accounts of the passive current financial obligations to maturity "and" Accrued Expenses Payable "of a company dedicated to service delivery in education in pre-primary levels, primary and secondary education for the year ended 31 December 2008. This work consists of six chapters. The first chapter shows the definitions and basic concepts of a financial audit to better understand the work. The second chapter presents a description and understanding of the audited company. The third chapter contains the audit planning, which details the company's financial situation by analyzing vertical, horizontal and financial ratios, which allowed us to determine the selected accounts liabilities. The fourth chapter was performed audit tests to selected accounts to determine their reasonableness. The fifth chapter presents the audit report with the opinion of the independent auditors. The sixth chapter contains the conclusions and recommendations of the audit.